Transformation of Pesantren Thought in Islamic Education: Genealogy of Discourse and Epistemic Adaptation in Indonesia - Muhammad Ikshanudin (Tarbiyah : Jurnal Ilmiah Kependidikan, 2026)
Pesantren is a central pillar of Islamic education in Indonesia. It does not merely reproduce religious values, but also actively shapes and transforms Islamic discourse in response to changing historical conditions. This article aims to analyze the transformation of pesantren thought through conceptual-analytical and historical-critical approaches across five major historical phases: early Sufism, Islamization-politics, colonialism, the post-independence period, and globalization. The study is based on library research on classical manuscripts, kitab kuning, and academic literature, and employs genealogical reading to uncover changes in epistemology, power relations, and pesantren adaptation strategies within Islamic education. The findings show that pesantren consistently develop an educational model that integrates tradition and modernity, spirituality and rationality, as well as texts and social praxis. The contribution of this article lies not only in rereading the intellectual history of Indonesian Islam, but also in offering a more critical, contextual, and transformative paradigm of Islamic education amid the challenges of globalization and the fragmentation of religious identity.